A retrospective view of ATM. - Kalmanek, Charles (Computer communication review.)
ATM was the focus of active research and significant investment in the early to mid 1990's. This paper discusses several visions for ATM prevalent at the time, and analyzes how ATM evolved during this period. The paper also considers the implications of this history for current connection-oriented technologies, such as optical transport networks and MPLS.